PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENANGGULANGI PERDAGANGAN GADING GAJAH ILEGAL THAILAND (2014-2018) - Manullang, Thania Tessalonika; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Illegal elephant ivory trade has become a serious threat to the sustainability of the world's elephant population. Thailand in particular has been known as one of the central areas of the ivory trade. This is a special concern for WWF as an international non-governmental organization that plays an important role in overcoming this problem. This study applies a qualitative approach with data collection techniques carried out through literature studies sourced from books, journals, and official websites of organizations that provide facts and data supporting the writing. This study applies a pluralism perspective which is used to explain how a non-state actor is able to play a role in collaborative action at the international level based on the theory of the Role of Non-Governmental Organizations related to the role of WWF as an NGO in tackling the illegal elephant ivory trade in a country. The results of the study show that WWF has played a significant role in reducing the number of illegal elephant ivory trade in Thailand through three main aspects, namely policy advocacy, increasing public awareness and education, and increasing the capacity of human resources involved in monitoring the elephant ivory trade. Keywords: Illegal Ivory Trade, WWF, Thailand.